KAJIAN TEKNIS PEMELIHARAAN SETTLING POND PADA PENGOLAHAN BJIH BESI, PT. KUATASSI, KABUPATEN SOLOK, SUMATERA BARAT - Maulana Assidikkey Iqra; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2021)
. PT. Karya Usaha Aneka Tambang Solok Selatan Indonesia has 6 settling pond. One thing that needs to be considered in deposition is the tailings and the dimensions of the settling pond, whether the pond is able to handle the waste that comes out of iron ore processing. The purpose of this study is to calculate the dimensions of the pond, calculate the percentage of deposition, calculate the period of dredging, calculate the length of dredging, and the costs that need to be incurred for pond maintenance.The method used in conducting this research uses the type of quantitative research. This is because in future research, data will be used in the form of numbers. The research was carried out by calculating the tailings entering the pond, taking water samples, calculating the dimensions of the pond, dredging the settling pond, the cycle time of the digging tool for dredging activities, and the cost of heavy equipment.The area and volume of the settling pond is 20345.3 m2 and the volume is 16,799.66 m3. With a depth of 0.3-0.95 m. After analyzing the maintenance cycle for pool 1 is 16.71 and pool 2 is 6.45 years. For pond dredging activities, the company uses one Hitachi zaxis 210f excavator and one Mitsubishi Fuso 220Ps Dump Truck with a total TSS tonnage transfer time of 1.17 days and a loading and digging time of 3.92 days with the dredging cost for pond 1 being Rp3,587,500. ,00. (three million five hundred eighty-seven thousand five hundred rupiah) and pool 2 is Rp. 13,511,000.00. (thirteen million five hundred and eleven thousand rupiah)